2017
DOI: 10.1038/s41559-017-0368-3
|View full text |Cite
|
Sign up to set email alerts
|

The winter pack-ice zone provides a sheltered but food-poor habitat for larval Antarctic krill

Abstract: A ntarctic krill Euphausia superba, a key species in Southern Ocean food webs 1 , plays a central role in ecosystem processes and community dynamics of apex predators, and is the target of a commercial fishery 2 . Krill spawn in late spring and their larvae develop during summer, autumn and under the ice in winter to emerge as juveniles in the following spring. The newly spawned eggs sink from the surface to up to 1,000 m depth where they hatch and the developing larvae actively swim upwards to feed in the upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 57 publications
0
121
2
Order By: Relevance
“…These were covered by our surveys only to a limited extent, owing to an even survey coverage across the area. With sea ice providing habitat for the overwintering of phytoplankton and krill, seasons of high winter ice extension typically support greater primary production than seasons with less ice-covered habitat in winter (Loeb et al, 1997;Meyer et al, 2017;Nicol et al, 2008). In all our survey years, very low ice concentrations were encountered in stratum WAP.…”
Section: Discussionmentioning
confidence: 84%
“…These were covered by our surveys only to a limited extent, owing to an even survey coverage across the area. With sea ice providing habitat for the overwintering of phytoplankton and krill, seasons of high winter ice extension typically support greater primary production than seasons with less ice-covered habitat in winter (Loeb et al, 1997;Meyer et al, 2017;Nicol et al, 2008). In all our survey years, very low ice concentrations were encountered in stratum WAP.…”
Section: Discussionmentioning
confidence: 84%
“…The importance of sea‐ice microbial community as food source for WG zooplankton is thought to increase during winter, although this pattern has been challenged by recent data. While some studies suggest that ice algae can provide up to 67% of the zooplankton carbon (Kohlbach et al, ), others conclude that pelagic production is more important as a food source and that sea ice mainly provides shelter (Meyer et al, ).…”
Section: Biology Ii: Food Web Of the Wgmentioning
confidence: 99%
“…Assuming typical densities of krill larvae in over‐rafted under‐ice habitats (mean 853 ind. m −2 , Meyer et al, ), this value would locally reach up to 13.6 mg C m −2 day −1 . The true feeding rates of krill larvae during our study may have been even lower, as suggested by Meyer et al (), albeit neglecting the large contribution of heterotrophic prey to the krill diet (Schaafsma et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…In our study region, water column Chlorophyll a and pigment concentrations are typically below 0.1 mg/m 3 between April and August (Comiso, McClain, Sullivan, Ryan, & Leonard, ; David et al, ), regardless of the presence of sea ice. Only in marginal ice‐zone blooms, Chlorophyll a concentrations reached 0.4–0.9 mg/m 3 (Meyer et al, ). Conversely, Antarctic bottom ice algal Chlorophyll a concentrations are higher by about one order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation